Athens students carrying wreaths in the funeral procession of University professor Lambrakis, Member of Parlement, assassinated following a speech in favour of nuclear disarmament. Probably published in The Student 7/8, vol.VII
Athens students carrying wreaths in the funeral procession of University professor Lambrakis, Member of Parlement, assassinated following a speech in favour of nuclear disarmament. Probably published in The Student 7/8, vol.VII.